USE OF THE NUMBER CATEGORY AND ITS ENGLISH AND UZBEK ANALYSIS - Mengniyozova Gulnora Toshtemirovna (American Journals Publishing, 2024)
This article describes the number category and its characteristics and comparison in several languages, the grammatical structure of the number category, and its expression in examples.
Keywords: Number category, grammatical category, plural, cryptography, unit, concept.